Building a Post Capitalist Economy and Religious Capitalism - Istianingsih Sastrodiharjo; Robertus Suraji (INQUISITIVE : International Journal of Economic, 2021)
This study aims to explore what the post-capitalist economic system and religious capitalism look like. This research also intends to prove whether the post-capitalist economic system and religious capitalism can be applied at this time. Currently, the economic system adopted by most countries in the world is a capitalist economic system. The economic system build by Adam Smith was originally based on religious values. In its journey, it turns out that this system has actually caused many problems, such as inequality of rich and poor, injustice, and even environmental destruction by companies. Facing this reality, some economists have proposed a more humanist and religious system to replace the capitalist economic system. They call this system the post-capitalist economic system and religious capitalism. They consider that capitalism is no longer adequate, especially in the face of a technology that is rapidly developing. Through research using this descriptive method, we look for how to build a post-capitalist economic system and religious capitalism. It is concluded that post-capitalist societies can arise as a result of spontaneous evolution when capitalism is no longer relevant. Post-capitalist societies need new norms and rules in order to run more humanist and religious. The new norms and rules are derived from the universal teachings of religion. Therefore, this economic system is called Religious Capitalism.